2007
DOI: 10.2478/s11532-007-0042-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photochromic behavior of some azo-polysiloxanes modified with nucleobases or donor-acceptor groups

Abstract: This paper presents the syntheses, characterization and photochromic behavior of some new azo-polysiloxanes modified with uracil, cytosine or nitro-phenolic groups. Taking into consideration the possibility of generating H-bonds or donor/acceptor interactions, this class of materials present a potential applicability in the immobilization of biomolecules and their nano-manipulations. Also, such compounds are capable of producing a fluid phase, with directional flowing capacity. For all these polymers, the mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Hurduc et al51, 52 utilized the same reaction conditions Sedlak et al used to functionalize an azopolysiloxane with either adenine, thymine, uracil, or cytosine as shown in Figure 8. The resulting nucleobase‐functionalized azopolysiloxanes were thermally more stable than the precursor53 and the authors investigated the photoisomerizations of the azobenzene in the resulting polysiloxanes 51, 54. Hurduc and coworkers54 demonstrated that the nucleobase‐functionalized polysiloxanes exhibited slower cis‐trans relaxation kinetics after UV trans‐cis isomerization which they attributed to the decreased mobility of the polymer chains resulting from the self‐complementary hydrogen bonding between the nucleobases.…”
Section: Nucleobase‐functionalized Polysiloxanesmentioning
confidence: 99%
“…Hurduc et al51, 52 utilized the same reaction conditions Sedlak et al used to functionalize an azopolysiloxane with either adenine, thymine, uracil, or cytosine as shown in Figure 8. The resulting nucleobase‐functionalized azopolysiloxanes were thermally more stable than the precursor53 and the authors investigated the photoisomerizations of the azobenzene in the resulting polysiloxanes 51, 54. Hurduc and coworkers54 demonstrated that the nucleobase‐functionalized polysiloxanes exhibited slower cis‐trans relaxation kinetics after UV trans‐cis isomerization which they attributed to the decreased mobility of the polymer chains resulting from the self‐complementary hydrogen bonding between the nucleobases.…”
Section: Nucleobase‐functionalized Polysiloxanesmentioning
confidence: 99%
“…The azopolymers were synthesized in two steps by nucleophilic substitution of chlorobenzyl groups with the sodium salt of 4-(phenylazo) phenol or 2,4-dinitrophenol as shown in Figure 1. More details concerning polymer synthesis can be found in our previous reports [29,30]. All polymers were characterized by 1 H-NMR, differential scanning calorimetry (DSC), UV spectroscopy and surface contact angle measurements.…”
Section: Experimental Partmentioning
confidence: 99%
“…A further increase in flexibility can be obtained by introducing not only the styrene, but a co-monomer (for example butyl acrylate) in the graftedchains. The second application refers to the use of the star-or brush-polysiloxanes as precursors obtaining azo-materials for optoelectronics and biology [21,22]. For this purpose, the chloromethyl styrene may be used as monomer, or co-monomer in ATRP grafting reactions.…”
Section: Introductionmentioning
confidence: 99%